PENGARUH KINERJA KEUANGAN TERHADAP PROFITABILITAS PADA PT. PELABUHAN INDONESIA I (PERSERO) - Taradiva Nabila; Ainun Zairinah (Jurnal Akuntansi dan Pembangunan (JAKTABANGUN) STIE Lhokseumawe, 2017)
This study aimed to examine the effect of asset growth and liquidity and simultaneous partial effect on profitability PT. Pelabuhan Indonesia I (Persero). The analytical method used in this research is multiple linear regression analysis. The results of this study indicate that (1) the regression coefficient value asset growth is not equal to zero, then H1 is accepted and can be interpreted that the asset growth effect on the level of profitability Return on Assets (ROA). (2) The value of the regression coefficient of liquidity is not equal to zero, then H1 is accepted and can be interpreted that the liquidity effect on the level of profitability Return on Assets (ROA). (3) Based on the draft terms of hypothesis testing to certify that the growth of liquidity of assets and the level of profitability Return on Assets (ROA) is the least. Referring to these requirements, the results of the study received Ha, ith it can be said that the growth of assets and liquidity simultaneously contributed to the increased profitability.